A Scoping Review of Exergames as a Digital Intervention for Active Aging - Irma Darmawati (Media Ilmu Keolahragaan Indonesia, 2025)
Exergames are a digital innovation that combines physical activity with interactive gaming, potentially enhancing the health and well-being of older adults. This scoping review aims to explore the effectiveness of exergames in supporting active aging. Data were collected from several academic databases, including PubMed, ScienceDirect, ProQuest, SAGE Journal, and EBSCO Host. The search was conducted using keywords such as "exergames", "digital intervention", "active aging", "older adults", "elderly", and "health benefits of exergames". The initial search yielded 441 studies, but after the screening process, 6 experimental studies were selected for further analysis. The findings indicate that exergames significantly improve balance, muscle strength, mobility, and cognitive function in older adults. Additionally, exergames contribute to increased motivation and social engagement in physical activities. However, the adoption of exergames in Indonesia remains limited due to low awareness, technological accessibility, and cultural adaptation challenges. Nurses play a crucial role in educating, facilitating, and integrating exergames into elderly healthcare services. Further research is needed to develop culturally appropriate exergames tailored to the needs of Indonesian older adults and to evaluate their long-term impact on quality of life.